Treatment of psychiatric disorders in the middle ages - Khrol, Natalia V. (Psychiatry, Neurology and Medical Psychology, 2020)
The article shows that medicine in the Middle Ages was based on the principles of scholasticism, which rejected any scientific discoveries and contrasted faith and science, which made its development impossible in general. Methods of treatment, used in medieval medicine, based on gross superstitions, reduced to the belief in the healing power of amulets and talismans; attributing to human health the location of stars; the role of conspiracies and the healing power of crushed stones and minerals. The medieval church linked the causes of disease with two main factors: illness, as God's punishment for human sins, and illness, as an obsession with evil forces. It is established that the basis of medieval medicine was primarily the teachings of the medieval church on the immortality of the soul, saints, diseases, which were dominated by gross pagan beliefs and philosophy, which made not only impossible the development of medicine as such, but also led to mass epidemics, unsanitary conditions, the growth of neuropsychiatric diseases, reducing the duration and quality of life. People with mental disorders have historically been either ignored or institutionalized. Their disorders were not easy to understand and therefore treat. Society often feared and carried out superstitions about people with mental illness that were based on culture and religious beliefs. Those who demonstrated evidence of mental illness were accused of committing sinful crimes and wrongdoings under the influence of the devil. Throughout history, the disease has been associated with demon possession or as punishment for some wrongdoing. Terrible surgeries aimed at freeing demons or healing the brain from disorders have been unsuccessful. Short periods of humane treatment have occurred throughout history. The very concept of disease, adopted in medieval medicine, according to the teachings of the papacy, reduced the disease either to God's punishment or to obsession. In both cases, no real medical understanding of the disease, and, consequently, the development of methods for diagnosis and treatment of diseases in principle was not necessary.